Fungistatic and fungicidal activity of bioactive compounds on the in vitro growth of Moniliophthora roreri (Agroindustrial Science, 2026)
Frosty pod rot, caused by Moniliophthora roreri, is one of the main constraints on cacao production in Latin America. Control strategies based on cultural practices and synthetic fungicides can be costly and pose environmental and health risks. This study evaluated in vitro the antifungal activity of the bioactive compounds (BCs) benzoic acid (BA), gallic acid (GA), catechin (CAT), quercetin (QUE), and β-carotene (BCA), as well as a mixture (MIX) of these compounds. Three concentrations (500, 1000, and 2000 mg L⁻¹) were tested on the mycelial growth of M. roreri. Data were analyzed using analysis of variance (ANOVA) followed by Tukey’s test (α = 0.05) and principal component analysis (PCA). The results showed that BA was the most effective compound, exhibiting a fungicidal effect at concentrations ≥1000 mg L⁻¹ and an IC₅₀ < 500 mg L⁻¹. BCA and GA showed dose-dependent fungistatic effects. CAT exhibited a hormetic response, whereas the MIX showed no synergistic effects. BA and BCA stand out as promising candidates for the development of biofungicides against M. roreri.
Keywords: Cacao frosty pod rot; secondary metabolites; phenolic acids; flavonoids; β-carotene